Design Of Administrative Service Information System With Waterfall Method At Balohili Gomo Village Office Based On Web - Sari, Ika Yusnita; Manalu, Mamed Rofendi; Laia , Bualazatulo (Jurnal Komputer Indonesia (Ju-Komi), 2023)
The era of the industrial revolution 4.0 as it is today, there has been a rapid development in the field of technology in various countries including in Indonesia itself. The development of technology in computer networks caused a rapid increase in the field of telecommunications marked by the emergence of the internet. This technological advancement requires agencies to follow technological developments and continue to improve their ability to manage data and information. Villages as the smallest part of the administrative government system in Indosenia, are required to be able to follow technological developments and continue to improve their ability to manage population administration data. Public services in Balohili Gomo Village include all services in the village or village such as the administrative field that serves the community in making a letter or other mail carrier. There are many types of public services in the village, especially in making correspondence and other matters related to the community in a village and in its implementation it is still not neatly organized, making it difficult to find letters needed by the community. Designing an administrative information system at the Balohili Gomo Village office is one of the objectives of this study.